THE SIGNIFICANCE OF INTERCULTURAL COMMUNICATION IN UNDERSTANDING STUDENTS’ OWN CULTURE - Nasiba Jakbarova; Nasiba Djakbarova; Nasiba Jakbarova (Western European Studies, 2024)
This study examines the importance of intercultural communication competence in today’s globalized world. The reasons why culture and language should be interconnected are explained in detail. The real-life cultural scenario is used to explain how intercultural communication helps learners to understand their own culture. The readers can use such authentic materials to develop their language skills and intercultural communication.
Keywords: communication; cultural elements